2018
DOI: 10.11606/s1518-8787.2018052016094
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à diarreia em menores de cinco anos, no estado de Pernambuco, segundo inquéritos realizados em 1997 e 2006

Abstract: OBJECTIVEDescribe and compare variations of the factors associated with the prevalence of diarrhea in children under five years old in the state of Pernambuco.METHODSWe used the databases of two population-based surveys from the years 1997 and 2006, with 2,078 and 1,650 children, respectively, evaluated in 18 municipalities of Pernambuco (Metropolitan Region of Recife, urban and rural interior). The variables, allocated at hierarchical levels, were analyzed using prevalence and Poisson regression ratios.RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
3
11
0
1
Order By: Relevance
“…Moreover, it is reported that water supply or treatment statistically played a significant role in reducing the risk of diarrhoea in children aged under 5. 6 , 10 This study also found that the child’s age group was significantly associated with the prevalence of diarrhoea. Diarrhoea was found to be more prevalent (34.9%) amongst children in the age group of 12–23 months.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, it is reported that water supply or treatment statistically played a significant role in reducing the risk of diarrhoea in children aged under 5. 6 , 10 This study also found that the child’s age group was significantly associated with the prevalence of diarrhoea. Diarrhoea was found to be more prevalent (34.9%) amongst children in the age group of 12–23 months.…”
Section: Discussionsupporting
confidence: 59%
“… 8 , 9 Nevertheless, factors such as residential area, unemployment, household income, mother or caregiver age, number of people per household, access to information, type of toilet facilities, access to safe drinking water, child immunisation status, nutritional status and number of sleeping rooms have been reported to contribute to diarrhoeal prevalence. 7 , 10 , 11 , 12 According to a study conducted by Thiam et al 6 in Mbour, Senegal, factors such as unemployment of mothers, use of shared toilets and no treatment of stored drinking water were found to be significantly associated with diarrhoeal prevalence. Equally, according to a cross-sectional study conducted in Eastern Ethiopia, major risk factors for diarrhoea included improper waste disposal practices, lack of handwashing facilities, living in rural areas, andpresence of two or more siblings in a household aged under 5 were found to be significantly associated with the prevalence of diarrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that children of older women have lower tendency of experiencing morbidity compared with children of young and middle-aged women. 18–20 This may be linked to the notion that older women are more experienced in child care practices than young and middle-aged women. Such experience may have contributed to the knowledge of these women in disease prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and the public were not involved in the design and conduct of this research. [18][19][20] This may be linked to the notion that older women are more experienced in child care practices than young and middle-aged women. Such experience may have contributed to the knowledge of these women in disease prevention measures.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…It can be categorized as acute or chronic diarrhea 6,7. Diarrhea still appears to be the main cause of child death in several countries, consisting of a discriminatory indicator of geographical areas characterized by precarious collective living conditions, typifying the so-called poverty ecosystem 8,9. In sub-Saharan Africa, diarrhea is the second most common cause of mortality and morbidity of under-five children.…”
Section: Introductionmentioning
confidence: 99%